Parasitismo de Thyca callista (Gastropoda: Capulidae) sobre Phataria unifascialis (Asteroidea: Ophidiasteridae) en el Golfo de California, México - Adriana Salazar; Héctor Reyes Bonilla (Revista de Biología Tropical, 1998)
The parasitism incidence of the gastropod Thyca callista on the asteroid Phataria unifascialis was measured in 500 asteroids from 11 localities off the southern Gulf of California, México. The intensity and prevalence of parasitism on P. unifascialis were 1.36 and 5%, respectively. In the study area, there was no significant relationships between latitude and parasite abundance, incidence and prevalence, but the sites where T. callista was most frequent were located near human settlements. Most T. callista were found adjacent to the starfish mouths, probably because it is easier for them to feed there.